A Novel Natural Antimicrobial Can Reduce the in vitro and in vivo Pathogenicity of T6SS Positive Campylobacter jejuni and Campylobacter coli Chicken Isolates - Sima, Filip; Stratakos, Alexandros Ch.; Ward, Patrick; Linton, Mark; Kelly, Carmel; Pinkerton, Laurette; Stef, Lavinia; Gundogdu, Ozan; Lazar, Veronica; Corcionivoschi, Nicolae (Frontiers in Microbiology, 2018)
Human campylobacteriosis is considered one of the most common foodborne diseases worldwide with poultry identified as the main source of infection accounting for 50-80% of human cases. Highly virulent Campylobacter spp., positive for the Type VI secretion system (T6SS), which have an increased ability to adhere to and invade the host gastrointestinal epithelium are highly prevalent in poultry. Multidrug resistant strains of bacteria is rapidly evolving and therefore, new antimicrobials to supplement animal feed that are able to control Campylobacter species, are in great need. The work presented herein indicates that a novel phenolic antimicrobial, Auranta 3001, is able to reduce the adhesion and invasion of human intestinal epithelial cells (HCT-8) by two T6SS positive chicken isolates, C. jejuni RC039 (p<0.05) and C. coli RC013 (p<0.001). Exposure of C. jejuni RC039 and C. coli RC013 to Auranta 3001 downregulated the expression of hcp and cetB genes, known as important in the functionality of T6SS. Furthermore, the reduced adhesion and invasion is associated with a significant decrease in bacterial motility of both isolates (p<0.05 – p<0.001) in vitro. Most importantly our in vivo results show that Auranta 3001 is able to reduce cecum colonisation levels from log 8 CFU/ml to log 2 CFU/ml for C. jejuni RC039 and from log 7 CFU/ml to log 2 CFU/ml for C. coli RC013. In conclusion this novel antimicrobial is able to reduce the pathogenic properties of T6SS campylobacters in vitro and also to decrease colonisation in vivo.